A Performance-Based Test for Assessing Students’ Online Inquiry Competences in Schools - Gonzalez-Ibanez, R; Escobar-Macaya, M (Springer Verlag, 2018)
In this paper, we introduce a performance-based test for measuring adolescents’ competences in online inquiry. The test covers four competence dimensions: (1) searching and selecting relevant sources, (2) identifying the main ideas presented in the sources, (3) evaluating the credibility of the sources, and (4) synthesizing information across the sources. We implement a technological solution called NEURONE to carry out this routine. The scoring of the test data is demonstrated by presenting preliminary results of a case study. Finally, we discuss the strengths and limitations of the test. © 2018, Springer International Publishing AG.